Immune Suppression Mediated by STAT4 Deficiency Promotes Lymphatic Metastasis in HNSCC - Anderson, Kelvin; Ryan, Nathan; Volpedo, Greta; Varikuti, Sanjay; Satoskar, Abhay R.; Oghumu, Steve (Frontiers in Immunology, 2020)
Head and neck squamous cell carcinoma (HNSCC) is a prevalent form of cancer with 5-year survival rates around 57%, and metastasis is a leading cause of mortality. Host-derived immunological factors that affect HNSCC tumor development and metastasis are not completely understood. We investigated the role of host-derived signal transducer and activator of transcription 4 (STAT4) during experimental HNSCC using an aggressive and metastatic HNSCC cell line, LY2, which was orthotopically injected into the buccal sulcus of wild type (WT) and STAT4 deficient (Stat4-/-) BALB/c mice. Necropsies performed at terminal sacrifice revealed that Stat4-/- mice displayed comparable primary tumor growth to the WT mice. However, the rate and extent of lymph node and lung metastasis among Stat4-/- mice was significantly higher. Downstream analyses performed on primary tumors, draining lymph nodes, spleens and bone marrow revealed significant upregulation of lymphocytic immunosuppressive biomarkers as well as an accumulation of granulocytic MDSC subpopulations in draining lymph nodes of metastatic Stat4-/- mice. Further, we observed a significant decrease in TH1, TH17 and cytotoxic activity in tumor bearing Stat4-/- compared to WT mice. Our results demonstrate that STAT4 mediates resistance to HNSCC metastasis, and activation of STAT4 could potentially mitigate lymphatic metastasis in HNSCC patients.